Hubungan Kepatuhan Konsumsi Tablet Tambah Darah (TTD) pada Ibu Hamil dengan Bayi Berat Badan Lahir Rendah (BBLR) di Wilayah Kerja Puskesmas Klakah - Suciati, Suciati; Sunanto, Sunanto; Ekasari, Tutik (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Nutrition is still a major health problem in Indonesia. The low nutritional status of pregnant women can result in various adverse effects for both mother and baby, including babies born with Low Birth Weight (LBW). One of the factors that influence LBW is Hb levels in pregnant women, therefore WHO recom-mends supplementation of iron tablets as part of ANC which can reduce the risk of LBW. The purpose is to determine the correlation between disciplinary of iron supplement consumption with LBW. This research uses spearman correlation studies. The samples are mothers whose babies under a year at Puskesmas Klakah area from July-August 2022 as 40 mothers. The data are acquired by using total sampling technique. The data used primary data (direct interview with the respondent) and secondary data. The result shows 14 babies with LBW and 26 babies born normally. The result of an interview about the discipline of iron supplement consumption during pregnancy shows that 16 mothers are disciplined and 24 mothers aren’t disciplined with iron supplement consumption. The Spearman test shows significant correlation between two variables with the α<0,05 (0,045). There is correlation between disciplinary of iron supplement consumption on pregnant mothers with babies born with LBW at Puskesmas Klakah Area.